Genome‐wide Association Studies Reveal Novel Locus With Sex‐/Therapy‐Specific Fracture Risk Effects in Childhood Cancer Survivors. (30th December 2020) - Im, Cindy; Li, Nan; Moon, Wonjong; Liu, Qi; Morton, Lindsay M; Leisenring, Wendy M; Howell, Rebecca M; Chow, Eric J; Sklar, Charles A; Wilson, Carmen L; Wang, Zhaoming; Sapkota, Yadav; et al.
ABSTRACT: Childhood cancer survivors treated with radiation therapy (RT) and osteotoxic chemotherapies are at increased risk for fractures. However, understanding of how genetic and clinical susceptibility factors jointly contribute to fracture risk among survivors is limited. To address this gap, we conducted genome‐wide association studies of fracture risk after cancer diagnosis in 2453 participants of European ancestry from the Childhood Cancer Survivor Study (CCSS) with 930 incident fractures using Cox regression models (ie, time‐to‐event analysis) and prioritized sex‐ and treatment‐stratified genetic associations. We performed replication analyses in 1417 survivors of European ancestry with 652 incident fractures from the St. Jude Lifetime Cohort Study (SJLIFE). In discovery, we identified a genome‐wide significant ( p  < 5 × 10 −8 ) fracture risk locus, 16p13.3 ( HAGHL ), among female CCSS survivors ( n = 1289) with strong evidence of sex‐specific effects ( p sex‐heterogeneity  < 7 × 10 −6 ). Combining discovery and replication data, rs1406815 showed the strongest association (hazard ratio [HR] = 1.43, p = 8.2 × 10 −9 ; n = 1935 women) at this locus. In treatment‐stratified analyses in the discovery cohort, the association between rs1406815 and fracture risk among female survivors with no RT exposures was weak (HR = 1.22, 95% confidence interval [CI] 0.95–1.57, p = 0.11) but increased substantially among those with greater head/neck RT doses (any RT: HR = 1.88, 95% CI 1.54–2.28, p = 2.4 × 10 −10 ; >36 Gray only: HR = 3.79, 95% CI 1.95–7.34, p = 8.2 × 10 −5 ). These head/neck RT‐specific HAGHL single‐nucleotide polymorphism (SNP) effects were replicated in female SJLIFE survivors. In silico bioinformatics analyses suggest these fracture risk alleles regulate HAGHL gene expression and related bone resorption pathways. Genetic risk profiles integrating this locus may help identify female survivors who would benefit from targeted interventions to reduce fracture risk. © 2020 American Society for Bone and Mineral Research (ASBMR).